The association between cognitive frailty and the risk of fall occurrence in older adults: a meta-analysis of cohort studies - Liu, Jian; Wu, Yu; Long, Zongke; Zhang, Simeng; Wu, Shicai (Frontiers in Medicine, 2025)
BackgroundCognitive frailty increases the risk of fall occurrence. However, previous studies have shown inconsistent correlations between cognitive frailty and the risk of fall occurrence.ObjectiveTo systematically review studies and explore the association between cognitive frailty and the risk of fall occurrence.MethodsDatabases were systematically searched. Meta-analysis was performed using RevMan 5.4 software after evaluation of the quality of the included studies by 2 researchers.ResultsA total of five studies including 16,962 patients were included. The results of Meta-analysis showed that the cognitive frailty group increased the risk of occurrence of falls in older adults [OR = 1.38, 95% CI (1.09, 1.73), p = 0.006]. Subgroup analyses showed that cognitive frailty in older adults increased the risk of fall occurrence using different cognitive frailty assessment tools, study participants from the community, different regions, and different sample sizes.ConclusionThe results of this study suggest that cognitive frailty in older adults is an independent risk factor for the occurrence of falls, and it is recommended that caregivers strengthen the assessment of cognitive aspects of older adults admitted to the hospital.